Humanitarian-Based Wage System Based On Constitution NRI 1945: Policy Evaluation Study Indonesian Wage System - Muhammad Addi Syirfan; Anik Kunantiyorini (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2021)
This research was compiled on the urgency of labor problems in the wage sector in Indonesia. The government based on the mandate of the law must realize the ideals of the nation, fulfill and protect the rights of its citizens, and strive to form a humane social sphere of society. This obligation is implemented through a set of rules that seek the values of Pancasila, especially human values and the 1945 NRI Constitution. The method used is a normative legal research method with a legal approach and a concept approach. This research is supported by secondary data that provides an overview of the discussion in the study. The formulation of the problem raised in this study is the concept of the ideal wage policy and how the humanitarian-based wage system. The result of this study is the concept of an ideal wage policy that is oriented toward fulfilling the welfare of workers and their families. However, the wage is still by the ability of entrepreneurs so that it remains balanced by considering the value of KHL. The humanitarian-based wage system emerged as a solution to labor law problems. This concept is one of the steps to construct legal norms of wage policy so that the content is based on human values as stated in the Second Precept of Pancasila. Keywords:  evaluation of upbringing; humanitarian dissemination; upbringing system; wages under the Constitution